Advances on Aptamers against Protozoan Parasites (2018)
ABSTRACT: Aptamers are single-stranded DNA or RNA sequences with a unique three-dimensional structure that allows them to recognize a particular target with high affinity. Although their specific recognition activity could make them similar to monoclonal antibodies, their ability to bind to a large range of non-immunogenic targets greatly expands their potential as tools for diagnosis, therapeutic agents, detection of food risks, biosensors, detection of toxins, drug carriers, and nanoparticle markers, among others. One aptamer named Pegaptanib is currently used for treating macular degeneration associated with age, and many other aptamers are in different clinical stages of development of evaluation for various human diseases. In the area of parasitology, research on aptamers has been growing rapidly in the past few years. Here we describe the development of aptamers raised against the main protozoan parasites that affect hundreds of millions of people in underdeveloped and developing countries, remaining a major health concern worldwide, i.e. Trypanosoma spp., Plasmodium spp., Leishmania spp., Entamoeba histolytica, and Cryptosporidium parvuum. The latest progress made in this area confirmed that DNA and RNA aptamers represent attractive alternative molecules in the search for new tools to detect and treat these parasitic infections that affect human health worldwide.